AB0192 Some of The Painful RA Patients Underrate Global Health VAS at Hospitals. (15th July 2016) - Kageyama, G.; Onishi, A.; Ueda, Y.; Kamei, Y.; Yamada, H.; Ichise, Y.; Waki, D.; Naka, I.; Tsuda, K.; Okano, T.; Takahashi, S.; Nishida, M.; et al.
Abstract : Background: Evaluating patient global VAS is one of the most essential process in RA practice. Despite reliability of patient global VAS being highly important in clinical practice, there has been no study comparing global VAS scores obtained at hospitals and those obtained at home where patients answer anonymously. Objectives: To compare the patient global VAS obtained before clinical examination in hospital with those answered anonymously at home. Methods: We asked RA patients to answer and mail the EQ5D data set anonymously. EQ5D consisted of 5 component questions (mobility, self-care, usual activities, pain/discomfort, anxiety/depression) and patient assessment global health VAS. EQ5D global VAS is anonymized patient global VAS evaluated at home. We compared the patient global VAS which is routinely surveyed at hospital before clinical examination with those surveyed anonymously at home. Results: The anonymized VAS score was higher than those routinely evaluated at hospital (p<0.0001). Global VAS scores obtained at hospital poorly correlated with those obtained anonymously at home (r=0.426). We compared patients who had higher patient global VAS at hospital than anonymized VAS at home with patients who had lower patient global VAS at hospital than anonymized VAS at home. Pain VAS scores remained to be risk factor to be higher anonymized VAS at home than those routinely evaluated at hospital after multivariate analysis. Conclusions: Discrepancy exists between patient global VAS evaluated in the hospital before clinical examination and those evaluated anonymously at home. There is a possibility that patients rating high pain VAS are underrating their global VAS scores at hospital. Disclosure of Interest: None declared